Emotional Intelligence as a Correlate of Senior Secondary School Students’ Academic Achievement in Biology in Awka South Education Zone - Obialor, C. O.; Okonkwo, H. C.; Eyaba, I. O.; Ndubuisi, A. E. (Journal of Research in Adult and Continuing Education, 2024)
The study investigated emotional intelligence as a correlate of senior secondary school students’ academic achievement in Biology in Awka South Education Zone. Three research questions were developed to guide the study. Three null hypotheses were formulated and tested at 0.05 level of significance. Correlational research design was used for the study. The population of the study comprised 1,956 students’ of senior secondary school two (SSII) in Awka South Education Zone. Simple random sampling technique was used in selecting the sample for the study. The sample size for the study comprised 100 SSII Biology students’. The research instrument was Students’ Grade Chart on Biology in Senior Secondary Schools (SGCBSSS) and adapted Emotional Intelligence Questionnaire (EIQ). The questionnaire was validated by two experts from the Department of Science Education and one specialist in Education Measurement and Evaluation, Faculty of Education, all in Nnamdi Azikwe University, Awka. The reliability of the instrument was carried out using test-retest method and calculated using Spearman’s Correlational Coefficient and a value of 0.76 was obtained. The data collected were analysed using Linear Regression and Regression ANOVA for hypotheses. The findings of this study revealed that there was a low positive relationship between the students’ emotional intelligence and their academic achievement in Biology. The findings of the study also revealed that there was no significant relationship between the male and female students’ emotional intelligence and their academic achievement in Biology. Based on the findings, it was recommended, among others, that educational administrators should adopt policies and educational programmes that support social and educational learning. In addition, teachers should be able to recognise and understand their own emotions as well as the emotions of their students in order to create conducive classroom learning experience.
Keywords: Emotional intelligence; academic achievement; Biology